2021
DOI: 10.3390/nu13092915
|View full text |Cite
|
Sign up to set email alerts
|

Nutri-Score and Nutrition Facts Panel through the Eyes of the Consumer: Correct Healthfulness Estimations Depend on Transparent Labels, Fixation Duration, and Product Equivocality

Abstract: Research on front-of-pack labels (FOPLs) demonstrated that Nutri-Score is one of the most promising FOPLs regarding healthfulness estimation accuracy. Nevertheless, as consumers are exposed to both the Nutri-Score and the mandatory Nutrition Facts Panel (NFP) in the supermarket, it is key to understand if and how both labels interact. This study investigates the contribution of Nutri-Score and NFP regarding healthfulness estimation accuracy, whether this impact differs depending on the product, and what role v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…These authors also showed that the simultaneous presence of bundled claims (health and nutrition) has a positive effect only when a nutritional claim is added in the presence of a detailed facts panel [28]. Furthermore, the combined presence of the Nutri-Score and the Nutrition Facts Panel produced a lower effect in assessing the product's healthfulness than did the presence of the Nutri-Score label alone [29].…”
Section: Literature Backgroundmentioning
confidence: 97%
“…These authors also showed that the simultaneous presence of bundled claims (health and nutrition) has a positive effect only when a nutritional claim is added in the presence of a detailed facts panel [28]. Furthermore, the combined presence of the Nutri-Score and the Nutrition Facts Panel produced a lower effect in assessing the product's healthfulness than did the presence of the Nutri-Score label alone [29].…”
Section: Literature Backgroundmentioning
confidence: 97%
“…In the present study, men stated to a greater extent that the Nutri-Score was easy to understand, providing the necessary information needed to be more reliable in people over the age of 50. According to Bossuyt et al, the presence of Nutri-Score on products can help the elderly make more accurate healthfulness valuations [27]. Also, according to the systematic review conducted by Hersey et al (2013), consumers can more easily interpret FOP food labels that incorporate text and symbolic color instead of labels that emphasize only numerical information, such as Guidance Daily Quantities, similar to RIs [28].…”
Section: Discussionmentioning
confidence: 99%
“…Medical aspects mortal FSAm-NPS cohort association weight cancer risk dietary FSA-NP hazard 9.7% Association between nutritional profiles of foods underlying Nutri-Score front-of-pack labels and mortality: EPIC cohort study in 10 European countries [149] Nutritional quality of food as represented by the FSAm-NPS nutrient profiling system underlying the Nutri-Score label and cancer risk in Europe: Results from the EPIC prospective cohort study [82] Food consumption based on the nutrient profile system underlying the Nutri-Score and renal function in older adults [52] [ 51-53,82,84,116,149- Improving the understanding of key nutritional elements to support healthier and more informed food choices: The effect of front-of-pack label bundles [166] Consumers' responses to front-of-pack nutrition labelling: Results from a sample from the Netherlands [36] Objective understanding of the Nutri-score front-of-pack label by European consumers and its effect on food choices: an online experimental study [167] [ 6,18,[33][34][35][36][37][38]78,97,102,105,111,117,142,154,155,160,161,163,164,[166][167][168][169][170][171][172][173][174][175][176] Note: * is used to include plurals, e.g., condition and condit...…”
Section: T8mentioning
confidence: 99%